Therapeutic role of aripiprazole in cartilage defects explored through a drug repurposing approach - Jun-Ku Lee; Hyunjeong Yeo; Sujin Choi; Kyeong Mi Kim; Hannah Kim; Sung-Sahn Lee; Hyun Il Lee; Younghoon Jeong; Hyun-Ju An; Soonchul Lee (Scientific Reports)
Abstract Articular cartilage has a limited regenerative capacity, resulting in poor spontaneous healing of damaged tissue. Despite various scientific efforts to enhance cartilage repair, no single method has yielded satisfactory results. With rising drug development costs, drug repositioning has emerged as a viable alternative. This study aimed to identify a drug capable of improving cartilage defects by analyzing chondrogenesis-related microarray data from the Gene Expression Omnibus (GEO) public database. We utilized datasets GSE69110, GSE107649, GSE111822, and GSE116173 to identify genes associated with cartilage differentiation, employing StringTie for differential gene expression analysis and extracting drug data from the Drug-Gene Interaction database. Additionally, we aimed to verify the cartilage regeneration potential of the identified drug through experiments using cellular and animal models. We evaluated the effects of aripiprazole on adipose-derived mesenchymal stem cells (ADMSCs) and chondrocytes using qRT-PCR and a 3D pellet culture system. In vivo, we assessed cartilage restoration by combining aripiprazole with a scaffold and implanting it into artificially induced cartilage defects in Sprague-Dawley rats. Subsequent mRNA sequencing provided insights into the mechanistic pathways involved. Our results showed that aripiprazole significantly increased mRNA expression of COL2A1 and SOX9, markers of chondrogenesis, and promoted chondrogenic condensation in vitro. Furthermore, aripiprazole effectively enhanced cartilage regeneration in the rat model. KEGG pathway and Gene Ontology Biological Processes (GOBP) analyses of the mRNA sequencing data revealed that aripiprazole upregulated genes related to ribosomes and cytoplasmic translation, thereby facilitating chondrogenesis. In conclusion, our findings suggest that aripiprazole is a promising candidate for improving damaged cartilage, offering a novel approach to cartilage regeneration.